ANALISIS DAN PERANCANGAN SISTEM PERSEDIAAN BARANG DAGANG DALAM RANGKA MENINGKATKAN PENGENDALIAN INTERNAL PERUSAHAAN (STUDI KASUS PADA DISTRIBUTOR CAT) - HIDAYAT, CHANDRA (Berkala Ilmiah Mahasiswa Akuntansi)
The success of a company in achieving its goal depends on the overall system that existed at its business processes especially in internal control systems and information systems. This study is a case study conducted in a distributor of paint which is a subsidiary of a paint factory in Bandung. Accounting information systems at the company's inventory system can be said to be inadequate so often result in inaccurate information and the long processing time, which in turn inhibits the process of selling and buying. Internal control in terms of inventory in a warehouse setting is also less risk sufficiently so it comes damaged and obsolete goods. The purpose of this research is to improve the existing system either manually or computerized in order to enhance the company's internal control. The data in this study were obtained through interviews, observation, and documentation. This study data analysis techniques using the system development life cycle (SDLC) which includes system analysis, conceptual design, and physical design. Phase analysis of this study includes analysis of the system of internal control by using the SAS 94, organizational structure analysis, reports and documents analysis, and analysis of system requirements. This analysis aims to identify weaknesses in the system inventory and how to overcome these weaknesses. Conceptual design include flowcharts and DFD inventory system. Physical design is the final step of this research which includes input, database (ERD) and outputs design and a computerized control of the input that aims to facilitate the process of making a more accurate inventory reports.